2021
DOI: 10.3390/en14227534
|View full text |Cite
|
Sign up to set email alerts
|

The Way of Usage and Location in a Big City Agglomeration as Impact Factors of the Nurseries Indoor Air Quality

Abstract: The quality of outdoor air in many places, especially in urbanized areas, is bad; therefore, a series of studies aimed at assessing the impact of outdoor air parameters on indoor air quality was conducted. Four nurseries (three buildings) located in different parts of Poznań, Poland were selected as research sites. During the research period, the concentrations of CO2, PM2.5, and PM10 inside and outside the buildings over time were analyzed. Measurements outside the buildings were supplemented with an analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…So, despite the operation of air purifiers, the amount of particulate matter in the indoor air could be even higher. Such a situation took place and has been confirmed by other research that was carried out in nurseries located in the same agglomeration as the studied school [33]. Although the research concerned facilities for smaller children, they can be treated as comparable, because nurseries are also facilities where a large number of people stay in a relatively small area.…”
Section: Discussionsupporting
confidence: 74%
“…So, despite the operation of air purifiers, the amount of particulate matter in the indoor air could be even higher. Such a situation took place and has been confirmed by other research that was carried out in nurseries located in the same agglomeration as the studied school [33]. Although the research concerned facilities for smaller children, they can be treated as comparable, because nurseries are also facilities where a large number of people stay in a relatively small area.…”
Section: Discussionsupporting
confidence: 74%
“…An adequate ventilation system is a must if there is a designated sleep room. Using another location for naps assists any CO2 concentrations that may have accumulated in the classroom during the learning period to decrease before the next session [41].…”
Section: Suggestionsmentioning
confidence: 99%
“…In nurseries A, B and D there is natural ventilation. Air quality tests conducted from December 2020 and June 2021 results are discussed in (Basińska et al, 2021). It has been shown that natural ventilation through airing and air inflow through Localisation of facilities as well as the climate parameters are described in Section S1 of Supplementary materials 2.2.…”
Section: Characteristics Of Nurseriesmentioning
confidence: 99%
“…In Poland, this problem occurs from October to April and it is related to the heating season. More detailed analyzes are presented in (Basińska et al, 2021). The conclusions from those studies indicate that airing the rooms, although it leads to a reduction in CO2 concentration, may deteriorate air quality in terms of particulate matter, which is not good for health.…”
Section: Accepted Manuscriptmentioning
confidence: 99%